Dermoscopy and reflectance confocal microscopy of pigmented actinic keratoses: a morphological study. (22nd April 2014) - Moscarella, E.; Rabinovitz, H.; Zalaudek, I.; Piana, S.; Stanganelli, I.; Oliviero, M. C.; Lallas, A.; Ardigo, M.; Cota, C.; Catricalà, C.; Mazzoni, L.; Pellacani, G.; et al.
Abstract: Background: Actinic keratoses (AKs) are very common lesions on sun damaged skin and, when pigmented, represent a challenge in the differential diagnosis with early melanoma. Non‐invasive diagnostic methods, such as dermoscopy and reflectance confocal microscopy (RCM) have been shown to improve the diagnostic accuracy of melanoma and non‐melanoma skin cancer, however, only one case report described confocal findings of pigmented AKs up to now. Objectives: The aim of our retrospective morphological study was to analyse dermoscopic and confocal images of a series of histopathologically proven pigmented AKs, located on the face and other body sites, to define peculiar features of these "difficult to diagnose" lesions. Methods: Clinical, dermoscopic and RCM images of 17 histopathologically confirmed pigmented AKs were retrospectively collected from the databases of four skin lesion clinics in Italy and USA. Dermoscopic and RCM images were analysed for prevalent morphological features. Results: The majority of the lesions were located on the face ( n  = 8); followed by scalp ( n  = 4) and trunk ( n  = 4); and one lesion was located on the lower limbs. On dermoscopy the majority of lesions were characterized by grey dots/globules/granularity and structureless brown pigmentation. The main RCM feature of pigmented AKs was as follows: (i) the presence of epidermal changes (atypical keratinocytes, parakeratosis, scaling); (ii) increased epidermal thickness; (iii) bright, small, dermal papillae with enlarged interpapillary space; and (iv) intraepidermal dendritic cells referrable to Langherans cells. Features suggestive of melanocytic lesions, such as nesting, meshwork pattern or atypical cells infiltrating the junction, were never detected in our case series at the dermal epidermal junction (DEJ) level. Conclusion: Larger case series with adequate control population are warranted to validate these findings and to test their value in clinical setting.